2011
DOI: 10.3390/nu3070712
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spirulina platensis versus Soybean on Insulin Resistance in HIV-Infected Patients: A Randomized Pilot Study

Abstract: HIV-infected patients develop abnormalities of glucose metabolism due to the virus and antiretroviral drugs. Spirulina and soybean are nutritional supplements that are cheap, accessible in our community and affect glucose metabolism. We carried out a randomized study to assess the effect of Spirulina platensis versus soybean as a food supplement on HIV/HAART-associated insulin resistance (IR) in 33 insulin-resistant HIV-infected patients. The study lasted for two months at the National Obesity Centre of Camero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
0
26
0
6
Order By: Relevance
“…Some authors advocate that insulin resistance is always present in these females [18] whereas others estimated the prevalence rate of insulin resistance to vary between 40% to 70% [19]. These results vary due to the diagnostic methods used [12] [20] [21].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some authors advocate that insulin resistance is always present in these females [18] whereas others estimated the prevalence rate of insulin resistance to vary between 40% to 70% [19]. These results vary due to the diagnostic methods used [12] [20] [21].…”
Section: Discussionmentioning
confidence: 94%
“…The sample size was determined using a pre-estimate change in insulin sensitivity of 20% between the two groups. The mean insulin sensitivity, M, of a normal non HIV-infected, non-diabetic Cameroonian population is M= 14.3 ± 2.2 mg/kg/min [12]. Choosing α (two-sided) at 0.05, a statistical power of 80%, the minimum sample size was 10 subjects per group.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have confirmed the beneficial effects of these factors in improving nutritional status, though mostly short termed and based on the use of nutritional supplements, which are expensive for HIV patients in resource limitted settings [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…That explains why the United Nations' Organisation for Food and Agriculture (FAO) gave special encouragement to African countries to resort to algae and more precisely microalgae in order to fight against hunger and malnutrition [1]. Spirulina, a multicellular blue alga, enriched with vitamins, minerals, and pigments [2][3][4][5][6][7][8] can easily be grown. Consumed since antiquity on the African and American continents, it is nowadays used in all the continents.…”
Section: Introductionmentioning
confidence: 99%
“…Burkina Faso, just like other countries, has made the production of spirulina an industry to fight against malnutrition, to contribute to the management of and help to people with HIV. Spirulina is used in persons with HIV because of its nutritional and immunostimulatory effects [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%